Few Liver-Infiltrating Cells Express CXCR3 in HIV/HCV Patients Commencing Antiretroviral Therapy. - Marini, S.; Susufi, Y.; Krisnuhoni, E.; Gani, R.; Yunihastuti, E.; Lee, Silvia; Tanaskovic, S.; Price, Patricia (Mary Ann Liebert, Inc., 2016)
Coinfections with Hepatitis C virus and human immunodeficiency virus accelerate the progression of both conditions and hamper effective treatment. Here we describe expression of CXCR3 on liver-infiltrating cells and peripheral T cells from coinfected patients commencing antiretroviral therapy (ART) in Indonesia. CXCR3 was expressed by small number of intrahepatic inflammatory cells, mostly in the portal areas. The number of cells did not change on ART and was markedly lower than the number of CD4(+) and CD8(+) cells in the liver. Data suggest that CXCR3 may contribute to liver infiltration but demonstrate a dynamic situation, changing as the immune system recovers on ART.